2015
DOI: 10.3904/kjim.2015.30.4.471
|View full text |Cite
|
Sign up to set email alerts
|

A combination of early warning score and lactate to predict intensive care unit transfer of inpatients with severe sepsis/septic shock

Abstract: Background/AimsThe modified early warning score (MEWS) is used to predict patient intensive care unit (ICU) admission and mortality. Lactate (LA) in the blood lactate (BLA) is measured to evaluate disease severity and treatment efficacy in patients with severe sepsis/septic shock. The usefulness of a combination of MEWS and BLA to predict ICU transfer in severe sepsis/septic shock patients is unclear. We evaluated whether use of a combination of MEWS and BLA enhances prediction of ICU transfer and mortality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
3
16
0
4
Order By: Relevance
“…It is common to find studies that analyze the use of EWS and lactate in people with acute disease [18,19,28] and studies that specifically analyze the association between the NEWS2 and lactate [20,21,29,30]. However, it is rather uncommon to find studies focused on the prehospital context [31][32][33], especially dealing with the use of the pLA for a further evaluation of risk groups stratified by the NEWS2.…”
Section: Discussionmentioning
confidence: 99%
“…It is common to find studies that analyze the use of EWS and lactate in people with acute disease [18,19,28] and studies that specifically analyze the association between the NEWS2 and lactate [20,21,29,30]. However, it is rather uncommon to find studies focused on the prehospital context [31][32][33], especially dealing with the use of the pLA for a further evaluation of risk groups stratified by the NEWS2.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Increased levels of the N-terminal prohormone of BNP have been shown to be associated with a dysfunction of the cardiovascular system and systemic inflammation. It was shown that a BNP decline over time implied a favorable outcome and lower mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical scores are not effective in early identification of infection in critically ill patients; however, combining these scores with biomarkers allows an early and accurate identification of sepsis. For example, Yoo and co-workers found that combining Modified Early Warning Score (MEWS), a tool for monitoring sepsis, with blood lactate levels was efficient for early identification of the disease [69]. The same was found by Bozza et al [70] and Oberholzer et al [71] when they combined the levels of MPC-1 or IL-6 with APACHE II, respectively, and found greater accuracy in the prognosis of the patients.…”
Section: Biomarker Combinationsmentioning
confidence: 77%